Effect of crop rotation in soil microorganisms (Mongolian Journal of Agricultural Sciences, 2021)
The aimed of this study was to effect of crop rotation on soil microorganisms activity, that’s soil biological indicator. Plots are Fallow-Wheat-Pea and Green manure fallow-Wheat-Oat+Melilotus of 3 fields rotation type. The study was conducted to determine the effect of crop rotation in soil biological indication is microbial active. Total number of microorganisms and nitrogen fixing bacteria determined in soil of three field rotation (Fallow-What-Peat, Green manure fallow-Wheat, Oat and Melilotus). The results of study in 2016-2019 in three field rotation – Peat, Wheat, Fallow were 85.6-96.9x106 CFU/g microorganisms. There were 87.5-89.3% bacteria and 10.6-12.4% actinomycetes. Rotation  fields of Oat and Melilotus, Green manure fallow, Wheat were 91.7-92.4 CFU/g microorganisms of it 82.1-84.4% bacteria and 15.5-17.8%-actinomycetes.Хөрсний бичил биетний идэвхид сэлгээний нөлөөг судалсан дүнХөрсний биологийн илтгүүр болох бичил биетний идэвхид таримлын сэлгээний үзүүлэх нөлөөг судлах зорилгоор 3 талбайт Уринш-Буудай-Вандуйн, Ногоон бордуурт уринш–Буудай–Овъёос+Донник бүхий таримлуудын сэлгээний хөрсөнд нийт бичил биетний тоог зүйлийн бүрэлдэхүүнээр, мөн азот шингээгч ашигтай бактерийн тоог тус тус тодорхойлов. 2016-2019 оны судалгааны дүнгээр ЭТС-ийн 3 талбайт Вандуй, Буудай (цуулбар) – Уринш хувилбарын 1 г хөрсөнд 85.6-96.9 сая.ш бичил биетэн, үүний 87.5-89.3%-ийг бактери, 10.6-12.4%-ийг актиномицет, 3 талбайт О+Д-НБУ-Буудайн сэлгээний 1 г хөрсөнд 91.7-92.4 сая.ш бичил биетэн, үүний 82.1-84.4%-ийг бактери, 15.5-17.8%-ийг актиномицет эзэлж байна. Түлхүүр үг: азот шингээгч, бактери, актиномицет, мөөгөнцөр